1987
DOI: 10.1042/bj2420721
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and site of inhibition of gluconeogenesis in rat liver cells by bacterial endotoxin. Stimulation of phosphofructokinase-1

Abstract: The characteristics and site of inhibition of gluconeogenesis by endotoxin were investigated in liver cells isolated from control and endotoxin-treated rats. Endotoxin treatment was associated with inhibition (40-50%) of gluconeogenesis from lactate plus pyruvate over a range of concentrations of substrate and of oleate and with or without glucose or glucagon. Similar inhibition was observed with asparagine, proline, glutamine, alanine and a substrate mixture, but not with glycerol, glyceraldehyde, dihydroxyac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
40
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 38 publications
15
40
2
Order By: Relevance
“…Despite the 3 -4-fold increase in phosphofructokinase activity in parenchymal cells incubated with conditioned medium from LPS-stimulatcd liver non-parenchymal cells in this study, the rate of glucose accumulation was not significantly decreased under these conditions. This contrasts sharply with the observation that the apparent rate of net gluconeogenesis from 10 mM lactate and 1 mM pyruvate in parenchymal cells isolated from endotoxintreated rats (in which carbohydrate flux through phosphofructokinase is stimulated 3 -4-fold) is only 60% of the rate in parenchymal cells from control rats [4]. The results of the present study suggest that endotoxin stimulation of parenchymal cell phosphofructokinase activity can be dissociated from the decrease in parenchymal cell glucose output.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite the 3 -4-fold increase in phosphofructokinase activity in parenchymal cells incubated with conditioned medium from LPS-stimulatcd liver non-parenchymal cells in this study, the rate of glucose accumulation was not significantly decreased under these conditions. This contrasts sharply with the observation that the apparent rate of net gluconeogenesis from 10 mM lactate and 1 mM pyruvate in parenchymal cells isolated from endotoxintreated rats (in which carbohydrate flux through phosphofructokinase is stimulated 3 -4-fold) is only 60% of the rate in parenchymal cells from control rats [4]. The results of the present study suggest that endotoxin stimulation of parenchymal cell phosphofructokinase activity can be dissociated from the decrease in parenchymal cell glucose output.…”
Section: Discussioncontrasting
confidence: 99%
“…does not directly stimulate carbohydrate flux through phosphofructokinase in isolated rat liver parenchymal cells. The rate of parenchymal cell [3-3H]glucose detritiation is increased, however, during incubation with conditioned medium from LPS-stimulated liver non-parenchymal cells to a magnitude similar to the 3 -4-fold increase in phosphofructokinase activity reported in parenchymal cells isolated 18 h following endotoxin administration in vivo [4].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…These findings confirm previous findings that LPS lowers blood glucose in animals and humans (35). Several mechanisms have been reported as to how LPS lowers blood glucose including enhanced systemic consumption of glucose (35), depletion of glycogen from liver and muscle (36), and impaired hepatic gluconeogenesis (37). Likely due to the extended time course of LPS-induced sickness in db/db mice (6), significant LPS-induced glucose lowering was seen in db/db mice at 8 h. Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It is also well known that LPS induces hypoglycemia in experimental animals as well as in humans (4,19,35). Incidentally, we have shown that various mitogenic substances other than LPS also induce hypoglycemia in mice (13).The mechanisms reported to underlie LPS-induced hypoglycemia include an enhanced systemic consumption of glucose (34), depletion of glycogen from liver and muscle (33,46), and impaired hepatic gluconeogenesis (18,26,33). The hyperthermic response often seen soon after LPS injection and the later hypothermic responses do not correspond well with the blood glucose changes induced by LPS (2, 28).…”
mentioning
confidence: 96%